Ar tebeaktualus ir ar tebemoteriškas „moterų rašymas“ - Kačkutė, Eglė (Literatūra, 2015)
The article is a speculation on whether the category of women’s writing continues to be applicable and/or indeed operative. It is argued that the effectiveness of women’s writing lies in identifiable trends, mutual influences and its particular heritage. A brief historical outline of women’s writing and criticism defines feminist literature as articulated by feminist criticism, whereas women’s writing is seen as a broad field of literary studies hardly restricted by any framework of interpretations. Women’s writing is said to be a part of and active participant in the literary process as a whole, and as such offers particular explorations in literature that have been overlooked, ventures into new ways of treating common topics, notably identity. Through the analysis of examples from contemporary French and British women’s prose, the article claims that although complex and ambiguous, the category of women’s writing remains a valuable lens through which to look at literary narratives written by women.